The Use of Complementary and Alternative Medicine among Cancerous Children: A Survey at Ali Asghar Children's Hospital - Shahla Ansari Damavandi; Neda Ashayeri; Amir Hesabi (Traditional and Integrative Medicine)
Survival rates for pediatric cancer patients have undergone rapid growth due to advancements in anticancer treatments. Despite these developments, cancer survivors continue to experience a range of persistent symptoms, including pain, fatigue, anxiety, depression, insomnia, and nausea/vomiting. Consequently, the use of complementary therapies has increased among this population as a means of alleviating these symptoms. This cross-sectional study involved 124 parents of children diagnosed with cancer and referred to Aliasghar Children’s Hospital in Tehran, selected via census sampling from January 2018 to January 2019. Data were collected using a validated and reliable questionnaire. Statistical analyses, including chi-square tests, Fisher’s exact test, and independent samples t-tests, were conducted to explore relationships between variables. A p value of < 0.05 was considered statistically significant, and data analysis was performed using SPSS version 25. Cronbach's alpha coefficient of this questionnaire was 0.85. Prior to diagnosis, 51.6% of patients reported using complementary medicine, which increased significantly to 77.4% after diagnosis. Herbal medicine emerged as the most commonly used form of complementary therapy. The primary motivation for using therapies was to manage chemotherapy side effects, reported by 83.3% of patients. The predominant barrier to the use of complementary medicine was insufficient knowledge regarding its benefits and risks. Notably, only one-third of mothers disclosed their children's use of integrative medicine to their physicians. The high prevalence of complementary medicine use among pediatric oncology patients underscores the necessity for healthcare providers to routinely inquire about such practices and educate patients about potential drug interactions. Additionally, the tendency for patients to conceal their use of complementary therapies from their healthcare providers warrants further attention and proactive engagement from clinicians.